Secondary metabolites isolated from Pinus roxburghii and interpretation of their cannabinoid and opioid binding properties by virtual screening and in vitro studies - Rola M. Labib; Radhakrishnan Srivedavyasasri; Fadia S. Youssef; Samir A. Ross (Elsevier, 2018)
Pinus roxburghii is highly popular as a potent analgesic and anti-inflammatory agent; however its exact mechanism of action was not fully elucidated. We aimed to interpret the analgesic and anti-inflammatory activity of the total ethanol extract of Pinus roxburghii bark (PRE) and its isolated compounds by both in silico molecular modelling and in-vitro cannabinoid and opioid binding activities evaluation for the first time. Comprehensive phytochemical investigation of PRE resulted in the isolation of sixteen compounds that were fully elucidated using 1H NMR and 13C NMR. Four of which namely 1,3,7-trihydroxyxanthone (1), 2,4,7-trihydroxyxanthone (2), isopimaric acid (9) and 3-methoxy-14-serraten-21-one (10) were first to be isolated from PRE. In silico molecular modelling was done using Accelry's discovery studio 2.5 on the cannabinoid receptor (CB1) and the different opioid receptors (mu, kappa and delta). Results showed that the different isolated constituents exhibited variable degrees of binding with the different examined receptors that undoubtedly explained the observed analgesic and anti-inflammatory activity of PRE. Thus in vitro evaluation of cannabinoid (CB1, CB2) and opioid (μ, κ, δ) binding activities for the isolated compounds was done. PRE and ursolic acid (11) showed a good CB1 receptor binding activity with 66.8 and 48.1% binding, respectively. Isopimaric acid (9) showed good CB2 and mu receptors binding activity estimated by 58.1 and 29.1% binding, respectively. Meanwhile, querectin-3-O-rhamnoside (7) exhibited a moderate κ-opioid receptor activity showing 56.0% binding. Thus, PRE could offer a natural analgesic and anti-inflammatory candidate through the synergistic action of all its components.